Exploring the Impact of Digital Transformational Leadership on Organizational Citizenship Behavior: The Mediating Role of Human Resources Analytics and Organizational Justice - Supinardi, Bambang; Subiyanto, Didik; Hadi, Syamsul (Universitas Muhammadiyah Pontianak, 2025)
Digital transformation (DT) has become a strategic element in the management of higher education institutions, especially since the COVID-19 pandemic accelerated the adoption of digital technologies. Universities are increasingly required to adjust their learning and administrative models by integrating advanced technologies. In this context, leadership plays a central role in fostering Organizational Citizenship Behavior (OCB)—voluntary behavior that is not formally required but contributes to organizational effectiveness. However, several studies indicate that leadership skills influence on OCB is inconsistent. Therefore, this study proposes an investigation into the impact of Digital Transformational Leadership (DTL) on OCB, with two mediating variables: Human Resources Analytics (HRA) and Organizational Justice (OJ). DTL combines transformational leadership characteristics with digital competencies, making it highly relevant in addressing the disruptions of the digital era. This research analyzes how DTL skills influence OCB through HRA and OJ and how these mediators enhance employee engagement and motivation. The study involved 184 lecturers from three faculties at the Indonesian Institute of the Arts Yogyakarta, selected proportionally using the Krejcie-Morgan method. A quantitative approach was employed with Stratified Random Sampling. Statistical analysis was conducted using SmartPLS 3 version 3.2.9. The findings show that DTL significantly influences Organizational Citizenship Behavior (OCB), Human Resources Analytics (HRA), and Organizational Justice (OJ). Additionally, the results indicate that Organizational Justice (OJ) significantly impacts OCB. However, Human Resources Analytics (HRA) does not directly influence OCB or as a mediating variableKeywords:Keywords: Digital Transformational Leadership, Organizational Citizenship Behavior, Human Resources Analytics, Organizational Justice, Digital Transformation